1987
DOI: 10.1111/j.1600-0528.1987.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus – a demographic study

Abstract: Among 20,333 Swedish people aged 15 yr and above, oral lichen planus was found in 1.9%; 1.6% among men and 2.2% among women. The highest prevalences were found in the age groups 65-74 and 55-64 yr. Reticular lichen planus was the most common type, found in 77.3%. The most prevalent intraoral location of lichen planus was the buccal mucosa, which was affected in 92%. Lichen planus was less prevalent among smokers than among non-smokers, except for the plaque type, which showed no difference in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
174
3
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(212 citation statements)
references
References 6 publications
21
174
3
6
Order By: Relevance
“…31,32 The reported prevalence ranges from 0.5 -2.2%. [31][32][33][34] More than one clinical form is frequently present at a time. Patients are usually between 30 to 60 years and 60% of patients with OLP are women.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The reported prevalence ranges from 0.5 -2.2%. [31][32][33][34] More than one clinical form is frequently present at a time. Patients are usually between 30 to 60 years and 60% of patients with OLP are women.…”
Section: Discussionmentioning
confidence: 99%
“…Lichenoid lesions of BM were clinically classified into reticular and erosive types, based on Axell's classification. 10 Biopsy specimens of the BM were obtained from lichenoid lesions in 15 of the patients. The biopsy of the LSG was performed as described by Greenspan et al 1 Heparinized peripheral blood samples were also obtained from 15 patients at the time of biopsy.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…Axell and Rundquist indicated that snuff users revealed a slightly higher prevalence of lichen planus than tobacco smokers. [15] However, Mani observed no relationship between lichen planus and oral tobacco habits. [16] Lichen planus in tobacco and betel users should not be ignored, even though malignant transformation potential of this lesion remains somewhat uncertain, because tobacco habits can influence the natural history of oral lichen planus.…”
Section: Discussionmentioning
confidence: 98%